Bos taurus haplotypes segregating in Nellore (Bos indicus) cattle - Utsunomiya, Y. T. [UNESP]; Fortunato, A. A.A.D. [UNESP]; Milanesi, M.; Trigo, B. B. [UNESP]; Alves, N. F. [UNESP]; Sonstegard, T. S.; Garcia, J. F. [UNESP] (Wiley, 2022)
Brazil is the largest exporter of beef in the world, and most of that beef derives from Nellore cattle. Although considered a zebu breed (Bos indicus), the history of Nellore cattle in Brazil is marked by the importation of bulls from India, the use of a Creole taurine (Bos taurus) maternal lineage to quickly expand the herds and backcrossing to Nellore bulls to recover zebu ancestry. As a consequence, the current Brazilian Nellore population carries an average taurine ancestry of approximately 1%. Although that percentage seems small, some taurine variants deviate substantially from that average, with the better-known cases being the PLAG1-Q haplotype involved with body size variation and the Guarani (PG) polled variant producing hornless animals. Here, we report taurine haplotypes in 9074 Nellore animals genotyped for 539 657 imputed SNP markers. Apart from PLAG1-Q and PG, our analysis further revealed common taurine haplotypes (>3%) spanning genes related to immunity, growth, reproduction and hair and skin phenotypes. Using data from 22 economically important traits, we showed that many of the major QTL previously reported in the breed are at least partially driven by taurine haplotypes. As B. taurus and B. indicus haplotypes are highly divergent, presenting widely different sets of functional variants, our results provide promising targets for future scrutiny in Nellore cattle.